DEPRESSION IN WOMEN IN THE GENERATIVE PERIOD AFTER TOTAL EXTIRPATION OF THE UTERUS - Belevska, Jana (Journal of Morphological Sciences, 2021)
The loss of the uterus after a hysterectomy has many negative psychological consequences for women who have undergone such an operation. Hysterectomy results in a loss of reproductive capacity, which is why in some countries the younger generation of women is not treated at all. Even for women who are sure that they do not want to have children in the future, the uterus as an organ is not seen as something that can be easily removed. Side effects of this surgery are loss of menstrual function, loss of reproductive function, impaired sexual function and distorted image of female identity. These changes can contribute to the development of negative emotional reactions, including depression. This paper presents research findings on the level of depression in women who enter the phase of removal of the uterus and women who have already undergone surgery, in order to gain insight into the psychological state of women who go through this process. Keywords : hysterectomy, depression, uterus https://doi.org/10.55302/JMS2141105b